2017
DOI: 10.1038/cdd.2017.78
|View full text |Cite
|
Sign up to set email alerts
|

RIP1 kinase activity-dependent roles in embryonic development of Fadd-deficient mice

Abstract: RIP1 is an essential regulator of TNF-induced signaling complexes mediating NF-κB activation, apoptosis and necroptosis. Loss of Rip1 rescues the embryonic lethality of Fadd or Caspase-8-deficient mice, even though the double knockout mice die shortly after birth like Rip1-deficient mice. Recent studies demonstrated that mice expressing RIP1 kinase-dead mutants developed normally and resisted necroptotic stimuli in vitro and in vivo. However, the impact of RIP1 kinase activity on Fadd embryonic development rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 52 publications
0
37
0
Order By: Relevance
“…Previous study reported by Liu et al showed that Rip1 Δ/Δ mice is more effective than Rip1 K45A/K45A mice in restoring embryonic lethality caused by FADD deficiency, which might attribute to their extents of inhibition on necroptosis 32 . In our study, we found that both RIP1 kinase-dead mutant mice(Rip1 K45A/K45A or Rip1 Δ/Δ ) had protective effects against cerebral injury after ischemic stroke, which were reflected in the reduction of infarct area and neurobehavioral score.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous study reported by Liu et al showed that Rip1 Δ/Δ mice is more effective than Rip1 K45A/K45A mice in restoring embryonic lethality caused by FADD deficiency, which might attribute to their extents of inhibition on necroptosis 32 . In our study, we found that both RIP1 kinase-dead mutant mice(Rip1 K45A/K45A or Rip1 Δ/Δ ) had protective effects against cerebral injury after ischemic stroke, which were reflected in the reduction of infarct area and neurobehavioral score.…”
Section: Discussionmentioning
confidence: 91%
“…To investigate the role of RIP1 kinase activity in acute ischemic stroke, two types of RIP1 kinase-dead mice ( Rip1 K45A/K45A and Rip1 Δ/Δ mice 32 ) were investigated by the MCAO/R model. In comparison with WT (wild-type) mice, infarct volumes in both Rip1 K45A/K45A mice and Rip1 Δ/Δ mice were significantly reduced (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As for the first condition, compelling experimental findings demonstrate that the concerted activity of CASP8, FADD, and c-FLIP L tonically inhibits necroptosis [ 432 , 466 , 478 , 479 482 484 ]. Thus, the embryonic lethality imposed on mice by the loss of Casp8 or Fadd can be rescued by concurrent ablation of Ripk3 or Mlkl , even though these double knockout animals generally display lymphoproliferative and/or systemic autoimmune disorders as adults [ 432 , 466 , 484 , 485 ]. Of note, Cflar −/− mice require the concomitant knockout of Ripk3 and Fadd to develop into adulthood, which underscores the inhibitory role of c-FLIP in both necroptosis and extrinsic apoptosis reported above [ 483 , 486 ].…”
Section: Necroptosismentioning
confidence: 99%
“…Receptor-interacting protein kinase 1 (RIPK1) is an important therapeutic target for the treatment of neurodegenerative diseases. Inactivation of RIPK1 by various genetic mutations, including D138N, K45A and ΔG26F27, leads to strong resistance to TNF and no other gross phenotype in mouse models 151154 . Furthermore, RIPK1 provides a pharmacologically ‘druggable’ target, as its kinase domain presents a hydrophobic pocket that is highly amenable for specific small-molecule inhibitors 155,156 .…”
Section: Fig 1 |mentioning
confidence: 99%